The impact of corporate governance and firm maturity on working capital management efficiency: Evidence from listed European firms - Kamel, Sarah Reda (AUC Knowledge Fountain, 2015)
The importance of studying working capital management efficiency (WCME) springs from its effect on a firm’s profitability, value, and solvency. The board of directors together with the Chief Executive Officer formulate corporate policies including those concerning working capital levels, yet it is management’s role to continuously monitor the various working capital components to strike an optimal balance amongst them. Accordingly, this study analyses the effect of corporate governance in overseeing management handling working capital levels. In addition, this paper studies the role of firm maturity as a determinant factor of WCME. For this purpose, the paper at hand uses 583 listed European firms from 2002 till 2013. And, it employs cross section random effect panel regression models, where various working capital characteristics are used as dependent variables. And, along with the explanatory firm maturity proxy and the corporate governance variables, we control for the effect of country and multiple firm-specific characteristics. Finally, this study suggests that both corporate governance (except for ownership concentration proxy) and firm maturity are significant factors of WCME. Yet, for some of the proxies used, we did not reach conclusive results regarding the direction of impact on working capital investment.